La lectura digital en la modalidad blended-learning. Una perspectiva educativa. - Quitián Bernal, Sandra Patricia; González Martínez , Juan (Colombian Applied Linguistics Journal, 2021)
Reading, as a cultural and cognitive activity, is present in the academic processes of children and young people of all educational levels, and particularly, in the blended-learning (b-l) modality. The ability required for reading in print or digital requires a process of training and theoretical-practical schoolwork, guided by teachers; since the ways of reading and approaching texts effectively are not inherent to the human being, it is necessary to learn them. Applying the Systematic Literature Review (RSL) method in a documentary corpus of 43 investigations carried out between 2012 and 2018, this review article presents some trends and characteristics about reading and its digital use in b-learning environments. Among the results, the incidence of Information and Communication Technologies (ICT) in the ways in which schoolchildren read and access information, as well as its mediating role in learning and the interaction of the reader with the text, stand out. However, the development of reading skills is not achieved as a direct consequence of the inclusion of technological resources in the b-l environment, whereby it is required to extend the research spectrum, in this regard, specifically in primary education.